2018
DOI: 10.1186/s12884-018-1683-7
|View full text |Cite
|
Sign up to set email alerts
|

Trajectory of vitamin D status during pregnancy in relation to neonatal birth size and fetal survival: a prospective cohort study

Abstract: BackgroundWe investigated the associations between vitamin D status in early and late pregnancy with neonatal small for gestational age (SGA), low birth weight (LBW) and preterm delivery. Furthermore, associations between vitamin D status and pregnancy loss were studied.MethodsSerum 25-hydroxyvitamin D (25OHD) was sampled in gestational week ≤ 16 (trimester 1 (T1), N = 2046) and > 31 (trimester 3 (T3), N = 1816) and analysed using liquid chromatography tandem mass spectrometry. Pregnant women were recruited at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 23 publications
4
47
0
Order By: Relevance
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
“…Because three studies [29][30][31] of 24 measured serum 25(OH)D concentrations at two or three periods of pregnancies, our meta-analysis included nine studies [28][29][30][31]36,39,41,44,46] in the first trimester, 11 studies [27,[30][31][32][33][34][35]37,38,40,43] in the second trimester, and nine studies [29][30][31]42,45,[47][48][49][50] in the third trimester.…”
Section: Search Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It appears that vitamin D intake from food and supplements contributed signi cantly to 25OHD level in population, in which sun exposure is minimum or dermal synthesis of 25OHD is limited. For instances, recent studies from two high latitude countries, Sweden [49] and Switzerland [34,47] reported that supplements use, but not time spent outdoors was associated with decreased risk of VDD. Likewise, in a large Chinese study, Yun and colleagues [40] demonstrated that vitamin D supplements use was associated with vitamin D status during winter when the sun exposure is limited but not signi cantly associated during autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, current considerable amount of literature has been published on the association of vitamin D insu ciency with a number of diseases [5,6,7,8,9,10]. Especially, the inadequacy vitamin D during pregnancy is associated with adverse outcomes for mothers and the fetus or consequences on the offspring [11,12]. Recently, a study showed that increased preconception vitamin D concentrations, not in early pregnancy, are associated with reduced pregnancy loss.…”
Section: Introductionmentioning
confidence: 99%